2019
DOI: 10.1155/2019/3621314
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified Porcine Mesenchymal Stem Cells by Lentiviral Tbx18 Create a Biological Pacemaker

Abstract: Background Tbx18 is a vital transcription factor involved in embryonic sinoatrial node (SAN) formation process but is gradually vanished after birth. Myocardial injection of lentiviral Tbx18 converts cardiomyocytes into pacemaker-like cells morphologically and functionally. In this in vitro and in vivo study, genetical modification of porcine bone mesenchymal stem cells (BMSCs) by recapturing the Tbx18 expression creates a biological pacemaker which was examined. Methods The isolated porcine BMSCs were transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…Transcription factors strongly expressed in SA have been studied for nearly 20 years as genes controlling cardiac automaticity. Not only SHOX2 [ 41 , 42 ] and HOXA2 [ 43 ] but also TBX18 [ 44 , 45 , 46 , 47 ], ISL1 [ 48 , 49 ], TBX3 [ 46 , 50 , 51 ], and TBX5 [ 52 ] have been reported. In our analysis, there were 81 SA-specific genes common to mice and humans, including seven transcription factors such as SHOX2 and HOXA2 , and TBX18 and ISL1 ( Supplementary File S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription factors strongly expressed in SA have been studied for nearly 20 years as genes controlling cardiac automaticity. Not only SHOX2 [ 41 , 42 ] and HOXA2 [ 43 ] but also TBX18 [ 44 , 45 , 46 , 47 ], ISL1 [ 48 , 49 ], TBX3 [ 46 , 50 , 51 ], and TBX5 [ 52 ] have been reported. In our analysis, there were 81 SA-specific genes common to mice and humans, including seven transcription factors such as SHOX2 and HOXA2 , and TBX18 and ISL1 ( Supplementary File S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although transcription factors that characterize the SA function have been intensively investigated for a couple of decades, these studies technically had to take into account the differences among animal species. For examples, TBX18 [ 44 , 45 , 46 , 47 ], TBX3 [ 46 , 50 , 51 ], and TBX5 [ 52 , 57 , 58 ] have been repeatedly reported as important transcription factors characterizing SA. Tbx18 is identified by in situ hybridizations from the superior vena cava to 75% of the SA head, and Tbx5 is expressed throughout the SA at 14.5 days of mouse embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work had identified that SAN development is tightly regulated by the transcription factors Shox2, TBX3, TBX5 and TBX18 [ 17 ]. Using these transcription factors, studies focused on overexpression to either increase the efficiency of the differentiation process of stem cells—either embryonic or induced-pluripotent-derived—into the pacemaker-like phenotype [ 33 , 34 , 35 , 36 , 37 , 44 , 45 , 46 ] or used a viral vector-mediated approach to demonstrate the conversion of cardiomyocytes into pacemaker-like cells [ 1 , 27 , 32 , 33 ]. Although all were successful to some degree, TBX18 was shown to be upstream of all these factors [ 25 , 26 ] and demonstrated the greatest potential in achieving functional pacemaker cells in either a stem cell or gene therapy context.…”
Section: Discussionmentioning
confidence: 99%
“…Newer attempts at using hTBX18 have attempted to use both gene- and gene-cell hybrid-based approaches to generate SAN-like pacemaker cells, both in vivo or in vitro, before implantation [ 32 , 33 , 34 , 35 , 36 , 37 ]. Further studies are required to assess the engraftment potential, pacing efficacy and any proarrhythmic effects of these strategies [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, for the purpose of circumventing the limitations and negative impacts of electronic pacemakers, stem cell-based biological pacemakers have been widely investigated so as to initiate the spontaneous activity of formerly quiescent cardiomyocytes [ 3 5 ]. Recent investigations have mainly focused on the induction of pacemaker-like cells through genetic reprogramming of stem cells [ 6 ]. The hyperpolarization-activated nucleotide-gated channel (HCN4) is the predominant isoform in the murine sinus atrial node (SAN) at both RNA and protein levels [ 7 ].…”
Section: Introductionmentioning
confidence: 99%